Repeatability and method-dependent variation of blood parameters in wild-caught Great Tits Parus major - Norte, A; Sheldon, B; Sousa, J; Ramos, J (2008)
When interpreting responses to experimental manipulations or particular environmental cues, it is necessary to have previous knowledge about the natural variation of the response traits. We studied how nine blood parameters, including four enzymatic activities, varied with time in wild Great Tits by assessing their repeatabilities over periods of 45 days, in the same season (Spring or Autumn/Winter), in the same year and over a four years period. The accuracy of the measurements of these blood parameters was also assessed. Measurement error reflected essentially sample and time of storage rather than assay effects. Hematocrit and haemoglobin had low repeatabilities within Spring, ranging from 0.26 to 0.31; Heterophil/Lymphocyte ratio (H/L), white blood cell count (WBC), total plasma cholinesterase and red blood cell glutathione peroxidase (GSH-Px) activities had moderate to high repeatabilities over periods of 45 days (repeatabilities ranged from 0.47 to 0.81 for GSH-Px and H/L, respectively), but also during longer periods such as during Spring (total plasma cholinesterase activity) and Autumn/Winter (WBC, H/L and GSH-Px). Of the blood parameters measured, total plasma cholinesterase, glutathione peroxidase and the haematological parameters WBC and H/L seem relatively constant and therefore reliable indicators of Great Tit's physiological condition within, at least, a 45 days time frame.